Screening and identification of two novel phosphate-solubilizing Pyrenochaetopsis tabarestanensis strains and their role in enhancing phosphorus uptake in rice - Bao, Xiaozhe; Lu, Haifei; Zhao, Jinyao; Yang, Taotao; Wu, Longmei; Zou, Jixiang; Chen, Qingchun; Zhang, Bin (Frontiers in Microbiology, 2025)
Low phosphorus (P) use efficiency significantly impacts rice yields. An environmentally friendly approach to increase phosphorus absorption and utilization in rice involves the exploration of phosphorus-solubilizing fungal resources. This study aimed to isolate and characterize fungal strains from the rice rhizosphere and assess their phosphate solubilization capabilities, plant-growth-promoting (PGP) traits, and mechanisms involved. An initial comparative sequence analysis of the hypervariable regions of the ITS rDNA and morphological analysis identified two strains belonging to the genus Pyrenochaetopsis, designated Pyrenochaetopsis tabarestanensis WFY-1 (PtWFY-1) and WFY-2 (PtWFY-2). Both strains demonstrated the ability to solubilize tricalcium phosphate, magnesium phosphate, phosphate rock powder, and calcium phytate phosphorus in vitro through acidification via the exudation of oxoglutaric acid, acetic acid, citric acid, and pyruvic acid. The amounts of oxoglutaric acid, acetic acid, citric acid, and pyruvic acid secreted were 1,900.03, 1,478.47, 579.11, and 685.90 mg L−1, respectively, for the PtWFY-1 strain and 2,441.67, 1,519.18, 867.65, and 888.30 mg L−1, respectively, for the PtWFY-2 strain relative to the control (0.00 mg L−1). These organic acids acidify the rhizosphere, increasing the availability of phosphorus for plant uptake. Inoculation with PtWFY-1 increased available soil P by 5.8% after 30 days, increasing the plant P concentration by 69.8% and the dry weight of the rice seedlings by 24.5%. Similarly, the PtWFY-2 strain increased these parameters by 7.7%, 60.3%, and 14.5%, respectively. PtWFY-1 showed slightly stronger effects on P availability and plant growth compared to PtWFY-2. The secretion of phytohormones was responsible for the growth promotion in rice by the PtWFY-1 and PtWFY-2 strains, along with P absorption The principal phytohormone in the PtWFY-1 and PtWFY-2 broths was L-tryptophan, which is a precursor substance for IAA synthesis, accounting for 84.68% and 83.46%, respectively. Assessment of the antifungal activities of the PtWFY-1 and PtWFY-2 strains against Magnaporthe oryzae demonstrated that rice grew healthier, indirectly promoting rice phosphorus absorption. These findings highlight the potential of using Pyrenochaetopsis strains as biofertilizers to sustainably improve phosphorus use efficiency in rice agriculture.